Remaja Hebat, Mental Kuat: Penyuluhan Manajemen Stres dan Kecemasan di SMA Katolik Untung Suropati - Selfya Ningrum; Dwike Primadita Rosanti (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
The community service program titled Great Youth, Strong Mentality at Untung Suropati Catholic High School aimed to enhance students understanding and skills in managing stress and anxiety, which are increasingly prevalent among adolescents due to academic pressures, social dynamics, environmental changes, and excessive exposure to social media. These issues are exacerbated by a lack of knowledge about effective stress management strategies, such as relaxation techniques and emotional communication, as well as the stigma surrounding mental health that discourages adolescents from seeking help. The counseling was conducted using an interactive approach, comprising a 30-minute informative lecture to explain the concepts of stress and anxiety, small group discussions (5–7 students) to encourage reflection and sharing of experiences, and practical exercises on relaxation techniques, such as diaphragmatic breathing and mindfulness, to provide hands-on experience. Supporting materials, including visual presentations and interactive quizzes, were utilized to enhance student engagement. Post-event evaluation revealed significant improvements in the understanding of stress and anxiety among students in grades X, XI, and XII. Students demonstrated enthusiasm through active participation in discussions and practical sessions, as well as positive feedback on the supportive and stigma-free environment. The program successfully equipped students with practical skills for stress management and fostered a healthier learning environment. For sustainability, it is recommended to conduct similar programs regularly, integrate mental health education into the school curriculum or extracurricular activities, provide concise modules for students’ independent use, and collaborate with school counselors to monitor technique implementation and offer ongoing support to ensure long-term impact on students mental well-being.